Refractive Surgery: Considerations in Forensic and Occupational Medicine: Doi: 10.36351/pjo.v38i4.1469 - Mauro, Salducci (Pakistan Journal of Ophthalmology, 2022)
In this brief communication, we will assess what issues are most forensic inherent in refractive surgery, devoting also to the general aspects of the problem, but without going into the specifics of individual cases or individual techniques. The current practice of a pre-printed signature below, often couched in general terms or formulated in an endless list of possible complications, serves more to define this event as bureaucratic and therefore as a consensus "documented" rather than "informed". Especially when this form is signed just before surgery, with the patient ready to be operated, is constantly interpreted by the judge as an act devoid of the meaning of information that enables the patient freedom of choice, which is seen instead as a safe conduct for the surgeon to protect against future challenges.